The effect of cytokines on osteoblasts and osteoclasts in bone remodeling in osteoporosis: a review - Xu, Jie; Yu, Linxin; Liu, Feng; Wan, Longbiao; Deng, Zhenhua (Frontiers in Immunology, 2023)
The complicated connections and crosstalk between the skeletal system and the immune system are attracting more attention, developing into Osteoimmunology. Wherein cytokines among osteoblasts and osteoclasts play a critical role in bone remodeling which is a pathological process in the pathogenesis and development process of osteoporosis. Those cytokines include tumor necrosis factor (TNF) family, Interleukin (IL) family, Interferon (IFN), chemokines and so on, most of which influence the bone microenvironment, osteoblasts and osteoclasts. This review summaries the effect of cytokines on osteoblasts and osteoclasts in bone remodeling in osteoporosis, aiming to providing latest reference to the immunology in osteoporosis.